930. Weakening the waves: Impact of a syndrome-based antimicrobial stewardship intervention during COVID-19. (15th December 2022) - Mena Lora, Alfredo J; Herald, Fischer; Lindsey, Brenna; Echeverria, Stephanie; Ali, Mirza; Burgos, Rodrigo M
Abstract: Background: Lower respiratory tract infections (LRTIs) from SARS-CoV-2 are difficult to distinguish from other viral or bacterial etiologies. This has led to increased antimicrobial use (AU) during the pandemic and concerns for concomitant rise in antimicrobial resistance (AMR). It is crucial for antimicrobial stewardship (ASP) to develop strategies to mitigate excess AU and curve AMR. We leveraged a syndrome-based ASP intervention targeting LRTIs and the use of anti-Pseudomonal beta lactams (APBL) during the COVID-19 pandemic. Methods: We incorporated COVID-19 elements into a syndrome-based prospective audit and feedback (PAF) at an urban community hospital. Elements included EMR order sets (Figure 1) that discouraged routine AU for COVID-19 and PAF targeting LRTIs and COVID-19 therapies. Empiric selection discouraging APBL was incorporated during the first COVID-19 wave. Order sets and PAF were then modified to reflect novel COVID-19 therapeutics and AU was strongly discouraged in subsequent waves. Data on AU and AMR from 2018-2022 was reviewed. Figure 1. Electronic medical records COVID-19 antimicrobial order set Results: Average quarterly AU increased during the first pandemic year by 8.7%, from 359.5 to 391 days of therapy per 1000 patient days (DOT/1000), with peaks 22.5% above the pre-pandemic average during COVID-19 surges. AU increased each COVID-19 surge, with smaller peaks each subsequent wave. DOT/1000 declined 29% from the first wave to the Omicron wave. AU decreased the second year to 318, an 18.6% decrease from the first pandemic year. Ceftriaxone use increased during surges, reflecting our LRTI guidelines (Figure 2). Peaks declined each subsequent wave, from a peak of 239 in the first wave to 75 during Omicron, a 68% decrease. The average monthly DOT/1000 for APBL decreased from 73.51 to 63.21 (Figure 3). Incidence rate of ESBL and CRE initially rose and then declined (Figure 4). Figure 2. Antimicrobial use (DOT/1000) before and during the COVID-19 pandemic Figure 4. Antipseudomonal beta lactam use before and during the COVID-19 pandemic Figure 5. Incidence of multidrug resistance organisms before and during the COVID-19 pandemic Conclusion: ASP successfully incorporated COVID-19 elements and steered AU during the pandemic. Though total AU increased, APBL use declined and AU peaks decreased with each COVID-19 wave, reflecting adherence with ASP recommendations. AMR increased during the first year and subsequently declined. ASP can play a vital role guiding AU during respiratory pandemics. Disclosures: All Authors : No reported disclosures.